Analisis Perbandingan Performa Golden Motor Magic Pie 5 dan Mitsuba M1048R sebagai Penggerak Kendaraan Listrik - Fikri, Marie; Okta, Malendra Fordry; Bagus, Awang (Rekayasa Mesin, 2015)
The main problem of electric vehicles are slow and expensive compared to conventional car. Because of that, it needs electrical motor that had the good performance and high efficiency. Brushless DC motor is the best electric motor. In this study, two brushless DC motor called Golden Motor Magic Pie 5 and Mitsuba M1048R was compared. Golden Motor Magic Pie 5 has lower efficiency of 78% compare to Mitsuba M1048R efficiency of 92%. However, the price Mitsuba M1048R 140 million is higher than Golden Motor Magic Pie 5.